PENGARUH PERCEIVED USEFULNESS, PERCEIVED TRUST, PERCEIVED SELF-EFFICACY, PERCEIVED EASE OF USE, DAN PERCEIVED SECURITY TERHADAP MINAT MENGGUNAKAN FINANCIAL TECHNOLOGY (Studi Pada Pengguna Fitur Layanan Go Pay di STIE Madani Balikpapan Tahun 2019): Oka Meliyana Fatimah Syamsiah STIE Madani Balikpapan - syamsiah, syamsiah (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2023)
This research aims to analyze the effect of perceived usefulness, perceived trust, perceived self-efficacy, perceived ease of use, and perceived security to interest in using financial technology go pay. The population of this research is STIE Madani Balikpapan students who have used go pay financial technology. The sampling technique uses purposive sampling and the total sample is 81 respondents. Data collection of this research used questionary method. Analysis method is Structural Equation Modeling (SEM) with Partial Least Square (PLS) and SmartPLS 3.0 as analysis tools. The results showed that perceived usefulness, perceived trust, and perceived security had a positive effect on interest in using go pay. While perceived self-efficacy and perceived ease of use do not affect the interest in using go pay.